EXTREMISM AS PRESENT-DAY MENACE TO THE RUSSIAN SOCIETY AND STATE - P. V. Volosyuk (Гуманитарные и юридические исследования)
The article deals with the causes and preconditions of the existence of extremist manifestations in Russia and some regions of the Russian Federation, which threatens national security. The author makes theoretical and practical suggestions aimed at prevention of extremist sentiments in the society.